2013
DOI: 10.1186/2193-1801-2-467
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary gland metastasis from rectal cancer: report of a case and literature review

Abstract: Pituitary metastases are unusual complications of malignancies. In about only 2% of patients they origin from colorectal cancer (CRC), with breast and lung as the most common primary tumors. Nevertheless, some authors reported a recent increase of the incidence of metastases in infrequent sites, such as brain or bone, arising from gastrointestinal cancers, probably due to the expanded treatment options and the resulting improved survival. Here, we report the case of a 54-year old woman diagnosed with lung meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Pituitary metastases, first described in 1857 (15), are a rare complication generally associated with advanced disease in cancer patients (15,17,18). The literature is mixed; however, on the basis of autopsy, it is generally reported that 1%-3.6% of cancer patients have pituitary metastases (17,19,20).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Pituitary metastases, first described in 1857 (15), are a rare complication generally associated with advanced disease in cancer patients (15,17,18). The literature is mixed; however, on the basis of autopsy, it is generally reported that 1%-3.6% of cancer patients have pituitary metastases (17,19,20).…”
Section: Discussionmentioning
confidence: 99%
“…The literature is mixed; however, on the basis of autopsy, it is generally reported that 1%-3.6% of cancer patients have pituitary metastases (17,19,20). Pituitary metastases represent only 1% of all pituitary lesions, but the percentage of all brain metastases represented by pituitary metastases has been reported to be as high as 28% (15,18).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations